The N-terminal region of acyl-CoA synthetase 3 is essential for both the localization on lipid droplets and the function in fatty acid uptake - Poppelreuther, Margarete; Rudolph, Berenice Mareen; Du, Chen; Vellaramkalayil, Regina; Becker, Melanie; Ehehalt, Robert; Füllekrug, Joachim (Journal of lipid research, 2012)
Cytosolic lipid droplets (LDs) are storage organelles for neutral lipids derived from endogenous metabolism. Acyl-CoA synthetase family proteins are essential enzymes in this biosynthetic pathway, contributing activated fatty acids. Fluorescence microscopy showed that ACSL3 is localized to the endoplasmic reticulum (ER) and LDs, with the distribution dependent on the cell type and the supply of fatty acids. The N-terminus of ACSL3 was necessary and sufficient for targeting reporter proteins correctly, as demonstrated by subcellular fractionation and confocal microscopy. The N-terminal region of ACSL3 was also found to be functionally required for the enzyme activity. Selective permeabilization and in silico analysis suggest that ACSL3 assumes a hairpin membrane topology, with the N-terminal hydrophobic amino acids forming an amphipathic helix restricted to the cytosolic leaflet of the ER membrane. ACSL3 was effectively translocated from the ER to nascent LDs when neutral lipid synthesis was stimulated by the external addition of fatty acids. Cellular fatty acid uptake was increased by overexpression and reduced by RNA interference of ACSL3. In conclusion, the structural organization of ACSL3 allows the fast and efficient movement from the ER to emerging LDs. ACSL3 not only esterifies fatty acids with CoA but is also involved in the cellular uptake of fatty acids, presumably indirectly by metabolic trapping. The unique localization of the acyl-CoA synthetase ACSL3 on LDs suggests a function in the local synthesis of lipids.
Gesehen am 14.08.2018